Wanderlust Borneo Travel / Abdul Ghaffar Naning... [et al.] - Sarama, Febiana; Idris, Mohamad Nazrin; Harun, Nurhanisah; Robert, Razzidin; Sunil, Suraidah; Naning, Abdul Ghaffar (2015)
This company runs a business relating to the tourism industry which it aims to provide tour and travel services. Basically, this company provides services like transportations and accommodations and also touring services for the convenience of all the clients especially the foreign tourists who have never been to Sabah, Malaysia.